1997
DOI: 10.1002/(sici)1097-4636(199705)35:2<137::aid-jbm1>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Glutaraldehyde crosslinking of collagen substrates inhibits degradation in skin substitutes grafted to athymic mice

Abstract: Collagen-based implants have been described as vehicles for transplantation of cultured skin cells for treatment of burn wounds. To optimize vascularization and repair of connective tissue, collagen solubility and glutaraldehyde crosslinking were evaluated. Cultured skin substitutes consisted of human keratinocytes and fibroblasts attached to collagen-glycosaminoglycan substrates that were prepared from acid-insoluble, or partially soluble collagen. Substrates were crosslinked with 0% or 0.25% glutaraldehyde, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 25 publications
0
35
0
1
Order By: Relevance
“…Although these sponges have the highest resistance to degradation in vitro, their inability to be cleared from the wound site in a timely manner may interfere with proper wound healing or delay vascularization. Other studies have demonstrated that GA cross-linked collagen scaffolds grafted to athymic mice are not cleared from the wound after 6 weeks of implantation and this persistence in the wound with may lead to a delayed development of connective tissue [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these sponges have the highest resistance to degradation in vitro, their inability to be cleared from the wound site in a timely manner may interfere with proper wound healing or delay vascularization. Other studies have demonstrated that GA cross-linked collagen scaffolds grafted to athymic mice are not cleared from the wound after 6 weeks of implantation and this persistence in the wound with may lead to a delayed development of connective tissue [38].…”
Section: Discussionmentioning
confidence: 99%
“…Acellular collagen scaffolds were prepared via freeze-drying and lyophilization as previously described [15] from comminuted bovine hide collagen (Kensey Nash; Exton, PA) and chondroitin-6-sulfate (GAG) (Sigma; St. Louis, MO) except without chemical cross-linking with GA [38]. Briefly, bovine collagen powder was solubilized in 0.5 M acetic acid and co-precipitated with GAG to yield a final concentration of 0.6%wt/vol.…”
Section: Collagen Scaffoldsmentioning
confidence: 99%
“…A nonexhaustive overview of the most recent publications, subdivided by application, for either collagen or gelatine alone or in a combination of other biopolymers is summarized in Table 2 which clearly indicates that gelatine has a wider-application range within the field of both soft and hard-tissue engineering. (Spira et al, 2004) skin replacement artificial skin dermis (Harriger et al, 1998) skin tissue engineering Tangsadthakun et al, 2006) artificial skin (Choi et al, 1999;Lee et al, 2003) soft tissue adhesives (McDermott et al, 2004) Surgery hemostatic agent (Cameron, 1978;Browder & Litwin, 1986) plasma expander suture wound dressing and repair (Rao, 1995) skin replacement (artificial skin) nerve repair and conduits blood vessel prostheses (Auger et al, 1998;McGuigan et al, 2006, Amiel et al, 2006 small intestine ( Chiu et al, 2009) liver -chitosan/gelatine scaffold (Jiankang et al, 2007) wound dressing (Tucci & Ricotti, 2001) nerve regenerationchitosan/gelatin scaffolds (Chiono et al, 2008) blod vesels ( Mironov et al, 2005) Orthopaedic born, tendon and ligament repair cartilage reconstruction -collagen (Stone, 1997), composite of collagen type II/chondroitin/hyaluronan (Jančar et al, 2007) articular cartilagecollagen/chitosan (Yan et al, 2010) bone substitutegelatine/hydroxyapatite (Chang et al, 2007) hard tissue regenerationgelatine/hydroxyapatite ( Kim et al, 2005) cartilage (Lien et al, 2010) cartilage defects regenerationchitosan/ gelatine (Guo et al, 2006), ceramic/ gelatine bone substitutegelatine/tricalcium phosphate (Yao et al, 2005) Ophthalmology corneal graft (Lass et al, 1986) vitreous implants artificial tears (Kaufman et al, 1994) tape and retinal reattachment contact lenses eye disease treatment (http.....) ocu...…”
Section: Collagen Vs Gelatine As Biomaterialsmentioning
confidence: 99%
“…Although the matrix incompletely forms the skin structure, it is applied for the wound bed, because a dermal substitute only functions as a guide for cells moving into the repair area, serves as a scaffold for cells such as fibroblasts, and helps to synthesize extra-cellular matrix (ECM) components. [26][27][28] Animal Tests. Figure 8 shows the histological results of acellular Gel100, cellular Gel100 and GHg721 scaffolds applied to the dorsal skin wound of athymic mice after one week of dressing.…”
Section: Resultsmentioning
confidence: 99%